Meal replacements followed by topiramate for the treatment of adolescent severe obesity: A pilot randomized controlled trial. Issue 12 (3rd November 2016) - Fox, Claudia K.; Kaizer, Alexander M.; Rudser, Kyle D.; Nathan, Brandon M.; Gross, Amy C.; Sunni, Muna; Jennifer Abuzzahab, M.; Schwartz, Betsy L.; Kumar, Seema; Petryk, Anna; Billington, Charles J.; Ryder, Justin R.; et al.
Abstract : Objective: To assess the safety and efficacy of short‐term meal replacement therapy followed by topiramate for body mass index (BMI) reduction in adolescents with severe obesity. Methods: Adolescents (ages 12–18 years) with severe obesity (BMI ≥1.2 times the 95th percentile or BMI ≥35 kg/m 2 ) were recruited for this double‐blind, randomized, placebo‐controlled trial. Participants completed 4 weeks of meal replacement therapy followed by randomization (1:1) to either 24 weeks of topiramate 75 mg/day or placebo. Mean changes were compared between groups. Results: Thirty adolescents (mean age 15.2 ± 1.7 years, mean BMI 40.3 ± 4.6 kg/m 2 ) completed the meal replacement phase and were randomized; 21 completed the study. The difference in mean percent change in BMI between the topiramate and placebo groups was not significant (−1.9%; 95% CI: −5.2% to +1.5%; P = 0.291). Significant improvements in visceral fat and very‐low‐density lipoprotein cholesterol were observed in the topiramate compared with the placebo group. There were no concerning changes in neurocognitive function or bone health. Conclusions: In this pilot study, 4 weeks of meal replacement therapy followed by 24 weeks of low‐dose topiramate compared with meal replacement therapy alone did not result in significant BMI reduction for adolescents with severe obesity.